Effects of prophylactic naps on physical fitness/exercise ability and executive function in healthy young trained males. Issue 3 (2nd April 2020) - Tanabe, Kosuke; Nakazato, Koichi; Noi, Shingo
ABSTRACT: This study examined the effects of prophylactic naps on physical fitness/exercise ability and executive function. Seven healthy trained males (mean age, 21.1 ± 0.4 years) participated in four experimental conditions (counterbalanced design): 90-min sitting rest (con condition); 30-min nap (nap30 condition); 60-min nap (nap60 condition); and 90-min nap (nap90 condition). Physical fitness/exercise abilities were assessed by grip/back strength, postural control, darts task, and the Wingate test. Executive function was assessed using simple reaction time (SRT), choice reaction time (CRT), and modified flanker tasks. Changes in oxyhemoglobin levels in the prefrontal cortex during the executive function tasks were monitored using near-infrared spectroscopy. None of the nap conditions (30, 60, 90-min) showed improvement in physical fitness/exercise abilities compared with the con condition. The nap30 condition showed shorter reaction times (RTs) in the SRT and CRT tasks than the con condition. The nap60 condition showed improved RTs in only the SRT task. The nap90 condition showed improved RTs in all executive function tasks. Increased oxyhemoglobin levels in the nap30 and 90 conditions were matched with improvement of each executive function tasks, but not in the nap60 condition. In conclusion, 90-min nap augmented the improvement of executive function tasks and activating the prefrontal cortex.